Sustainable production inventory model with greening degree and dual determinants of defective items. (20th September 2022) - Gautam, Prerna; Maheshwari, Sumit; Jaggi, Chandra K.
Abstract: In the world of environmental scarcity, customers are keen to invest in a supply chain player who makes environmentally sound choices. Owing to this, the present study develops a production inventory model with demand dependent on greening degree and price. The production process is faulty and thereby some fraction of defective items gets piled up along with the perfect products. Efficient management of defectives is indeed crucial in achieving sustainable development goals. Thus, the proposed study develops two models to handle the fraction of defective goods. The first model considers the salvaging of the defectives, which is quite applicable to the goods that are not suitable for any further dispensation. The second model considers the reworking option, which is pragmatic for most of the reworkable inventory goods. A sustainability assessment of both models is done and findings suggest the better performance of the second model. Numerical analysis is presented to impart the validity of the proposed study. A comprehensive sensitivity analysis is also done to demonstrate model features. The developed study is inspired by the recent advancements in the global supply chains in terms of greening levels. The key contribution lies in the framework of decision-making of various manufacturers and analyzing the impact of greening degree and pricing. With dual maneuver options for the defective items, the problem throws thought-provoking insights into the strategies of manufacturers and their vital decisions. Lingo and Mathematica software are used to solve the developed model. The present study contributes to the burgeoning field of sustainable supply chains by incorporating green and price-sensitive demand, carbon emissions, and dual options for handling defectives.